Fault-Aware Adversary Attack Analyses and Enhancement for RRAM-Based Neuromorphic Accelerator - Shang, Liuting; Jung, Sungyong; Li, Fengjun; Pan, Chenyun (Frontiers in Sensors, 2022)
Neural networks have been widely deployed in sensor networks and IoT systems due to the advance in lightweight design and edge computing as well as emerging energy-efficient neuromorphic accelerators. However, adversary attack has raised a major threat against neural networks, which can be further enhanced by leveraging the natural hard fault in the neuromorphic accelerator that is based on resistive random access memory (RRAM). In this paper, we perform a comprehensive fault-aware attack analysis method for RRAM-based accelerators by considering five attack models based on a wide range of device- and circuit-level nonideal properties. The research on nonideal properties takes into account detailed hardware situations and provides a more accurate perspective on security. Compared to the existing adversary attack strategy that only leverages the natural fault, we propose an initiative attack based on two soft fault injection methods, which do not require a high-precision laboratory environment. In addition, an optimized fault-aware adversary algorithm is also proposed to enhance the attack effectiveness. The simulation results of an MNIST dataset on a classic convolutional neural network have shown that the proposed fault-aware adversary attack models and algorithms achieve a significant improvement in the attack success rate.